An Open Effectiveness Trial of a Multimodal Inpatient Treatment for Depression and Anxiety Among Adults With Serious Mental Illness. Issue 1 (2nd January 2017) - Fowler, J. Christopher; Clapp, Joshua D.; Madan, Alok; Allen, Jon G.; Frueh, B. Christopher; Oldham, John M.
Abstract : Objective : This prospective open effectiveness trial examined symptom change trajectories and rates of remission from depression and anxiety in an intensive multimodal inpatient treatment for adults with serious mental illness (SMI). Patient baseline characteristics were examined as mediators/moderators of treatment response. Methods : Adult inpatients with SMI ( N  = 994) completed an average of 39 days of inpatient treatment. Latent growth curve (LGC) methods were used to model symptom trajectories, estimating expected remission based on individual patterns of change observed across the sample. Results : Absolute reductions in symptoms were substantial, with large effect size improvements for both depression ( d  = 1.21, 95% CI [1.13, 1.29]) and anxiety ( d  = 1.13, 95% CI [1.05, 1.21]). For those presenting with elevated depressive symptoms (Patient Health Questionnaire-Depression ≥ 5.0; 87.5% of the sample), 46.9% evidenced remission from admission to discharge. Among patients presenting with significant anxiety (Patient Health Questionnaire–Generalized Anxiety Disorder Screener ≥ 5.0; 84.5% of the sample), 50.0% evidenced remission from admission to discharge. Mediation analyses revealed that depression and anxiety severity decreased more rapidly with increasing age and initial levels of experiential avoidance. Conclusions : Rates of remission of depression and anxiety were greater than anticipated in this large cohort of adult SMI inpatients and may be related to intensity and length of hospitalization.